Installation of an axial Pump-as-Turbine (PaT) in a wastewater sewer of an oil refinery: A case study. (15th September 2019) - Renzi, Massimiliano; Rudolf, Pavel; Štefan, David; Nigro, Alessandra; Rossi, Mosè
Graphical abstract: Highlights: Axial Pump-as-Turbine (PaT) as energy recovery application in oil refineries. A branch of the groundwater's wastewater sewer is analysed to use the axial PaT. CFD simulations were performed to investigate PaT's performances. The system in the case study allows to save 1706 €per year. The PayBack Period of this energy efficiency intervention is about 1 year and 10 months. Abstract: This paper analyses an energy recovery solution based on the Pump-as-Turbine (PaT) technology applied in an oil refinery. Since under-ground water might be contaminated by the chemical processes, an intervention named "Pump & Treat" was adopted in the studied oil refinery to reclaim the installation site and to safeguard the zones nearby. After the groundwater's treatment is performed by a specific water treatment plant, part of the wastewater is discharged, by gravity, into the sea through a sewer. In this work, the installation of an Axial Flow Pump (AFP) is studied for a branch of the wastewater sewer and its use as turbine for energy recovery purposes is evaluated. Knowing both flow rate and available head inside the sewer, which were used as Best Efficiency Point (BEP) values, a proper axial PaT design was identified in the ANSYS® Workbench and Computational Fluid Dynamics (CFD) simulations of the axial PaT design were performed in both pump and turbine modes. The obtained results were used to scale down the hydraulic machine and the new scaled axial PaT was simulated and analysed in detail by means of steady CFD simulations. The characteristic curves as well as the efficiency ones of the PaT are reported and an insight of the internal fluid flow is carried out. Finally, the installation of the designed PaT was analysed and discussed from both technical and economic points of views, allowing to achieve an economic saving of about 1706 €/year that lead to a PayBack Period (PBP) of about 1 year and 10 months.